2000
DOI: 10.1590/s0104-79302000000200006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory action of propolis on macrophage activation

Abstract: Propolis has been the subject of several recent studies, with the aim of elucidating its biological and pharmacological properties. Propolis has a well-known antimicrobial activity as well as antioxidant, antitumoral, antiinflammatory, and regenerative properties, but literature about its effects on the immune response is scarce. The goal of this work was to evaluate the propolis effect on macrophage activation by oxygen (H2O2) and nitrogen (NO) metabolite determination. Propolis was produced by africanized ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 13 publications
7
105
0
19
Order By: Relevance
“…Propolis extracts can act on the nonspecific immune response by activating macrophages, inducing the release of hydrogen peroxide, and inhibiting the production of nitric oxide in a dose-dependent manner (Orsi et al, 2000). The latter it may be explained by the fact that propolis inhibits both inducible nitric oxide synthase (i-NOS) expression and the catalytic activity of i-NOS (Tam-no et al, 2006).…”
Section: Anti-inflammatory and Immunomodulatory Response To Propolismentioning
confidence: 99%
“…Propolis extracts can act on the nonspecific immune response by activating macrophages, inducing the release of hydrogen peroxide, and inhibiting the production of nitric oxide in a dose-dependent manner (Orsi et al, 2000). The latter it may be explained by the fact that propolis inhibits both inducible nitric oxide synthase (i-NOS) expression and the catalytic activity of i-NOS (Tam-no et al, 2006).…”
Section: Anti-inflammatory and Immunomodulatory Response To Propolismentioning
confidence: 99%
“…Entretanto, a produção de NO estimulada por Con A foi menor nos grupos tratados com EHP quando comparados ao controle. Estes resultados estão de acordo com alguns trabalhos que mostram que extratos de própolis inibem a produção de NO por macrófagos estimulados com lipopolissacarídeos (LPS) bacterianos ou IFN-γ, dependendo da dose (Moriyasu et al, 1994;Orsi et al, 2000). A produção de NO em tumores sólidos experimentais pode facilitar a permeabilidade vascular e o rápido crescimento do tumor (Maeda & Akaike, 1998), enquanto uma baixa produção deste metabólito pode causar um efeito oposto.…”
Section: Discussionunclassified
“…Estudos farmacológicos têm demonstrado que a própolis de A. mellifera aumenta a atividade das células Natural Killer (NK) inibindo o crescimento das células tumorais e modula in vitro e in vivo a produção de óxido nítrico (NO) e a liberação de peróxido de hidrogênio (H 2 O 2 ) por macrófagos peritoneais (Orsi et al, 2000). O ácido cinâmico isolado da própolis atua tanto na imunidade inata quanto na imunidade adquirida, estimulando a proliferação de linfócitos e induzindo a produção de citocinas (Ivanovska et al, 1995).…”
Section: Introductionunclassified
“…Martinez Garcia et al (14) ;Duailibe et al (15) Clinical -Antimicrobial action Azevedo et al (4) ;Santos et al (11) ; Lofuto et al (35) Clinical -Therapeutic action in wound healing Peruchi et al (2) ;Park et al (3) ;Vargas et al (5) ; Fernandes Júnior et al (6) ; Silva et al (7) ;Sforcin et al (8) ; Sforcin et al (9) ;Oliveira et al (10) ; Auricchio et al (35) ; Fernandes Júnior et al (17) ;Machado et al (18) ;Longhini et al (19) ;Sawaya et al (20) ;Fernandes et al (21) ;Fernandes Júnior et al ( 22) ; Muli et al (23) ;Gebara et al (24) ;Fernandes Júnior et al (25) ;Bianchini et al (26) ;Gonçales et al (27) ;Dantas et al (28) ; Ayres et al (29) ;Orsi et al (30) ;Orsi et al (31) ;Sforcin et al (32) ;Sforcin et al (33) ;Orsi et al (34) ; Fernandes Júnior et al (36) ;Fernandes et al (37) ; Araújo et al (38) Experimental -Antimicrobial action Rahal et al (16) Experimental -Therapeutic action in wound healing (1) . Another study, which used propolis ointment on 22 chronic wounds, of which 11 were venous ulcers, seven pressure ulcers, two diabetic ulcers, and two post-trauma injuries, found that necrotic tissue was present in 14 (8.2%) during tissue assessment process.…”
Section: Thematic Focus Approachmentioning
confidence: 99%